Comparative analysis of liverworts flora of mountains in the Lapland State Nature Reserve (Murmansk Region, Russia) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
The liverworts flora of the Lapland State Nature Reserve includes 173 species that is 63% of the liverworts biodiversity of the European part of Russia, 66.5% of the North-West of Russia, and 88% of the Murmansk Region. The species diversity of partial liverworts floras of the Lapland State Nature Reserve Mountains varies but slightly: 139 species were found in the Salnye Tundry Mts, 124 species in the Monche-tundra Mts, 133 species in the Chuna-tundra Mts, and 112 species in the Nyavka-tundra. The high diversity observed in the studied sub-regions can be explained by diverse geological, geomorfological and climatic conditions of the area, as well as by intensive research; fairly dense and uniform coverage of liverworts sampling in the area.
Keywords: Lapland State Nature Reserve, flora, diversity of liverworts.